PENERAPAN MODEL ACTIVE LEARNING TIPE CARD SORT UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA SISWA KELAS VI SD NEGERI 005 TELUK SEBONG - Efiza Yanita; Zulhidir Zulhidir (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
The problem in this research is the low activity and learning outcomes of mathematics students of grade VI SD Negeri 005 Teluk Sebong. The purpose of this study was to increase student learning activities and outcomes through the card sort type of active learning model. This type of research is classroom action research. The research was carried out in two cycles. Each cycle consists of the stages of planning, implementing, observing, and reflecting. Data was collected through observation and tests using observation sheets and test questions. Data analysis using qualitative and quantitative analysis. The results showed that the card sort type of active learning model was easy for teachers to implement, as evidenced by an increase in teacher performance scores. The performance value of the teacher's cycle I is in the good category and cycle II is in the very good category. The results of this study prove that the application of the card sort type of active learning model in mathematics learning can increase student activity and learning outcomes. The increase in student learning activity can be seen from the percentage of student learning activity, cycle I with the active category and increases in cycle II with the very active category. The value of student learning outcomes cycle I with good category and cycle II with very good category. Completeness of student learning outcomes cycle I as many as 13 students in the good category and Cycle II increased to 18 students in the very good category.